ANALISIS DEIKSIS DALAM BAHASA GORONTALO - Hamzah, Aryati; Mooduto, William I. S.; Mashudi, Imam (Universitas Muhammadiyah Surakarta, 2021)
This research aims to describe the use of deixis in Gorontalo Language. This research was conducted in two stages namely the stage of preparation and implementation of the research. This research was conducted for 1 year. The result of the research showed that the form and meaning of deixis are person deixis, time and place. Persona deixis is divided into several types is deixis of first-person singular (wa’u ‘1sg’, watiya ‘1sg’), deixis of the first person plural (ami ‘1pl.excl’), deixis of the second person singular (yi’o ‘2sg’, tingoli ‘2sg’), deixis of the second person plural (tingoli ‘2pl’, timongoli ‘2pl’), and deixis of the third person singular (tio ‘3sg’) and timongolio ‘3pl’ as a deixis of the third person plural. Whereas, deixis of place are teye, teyamai ‘here’, tetomota ‘there’ this means to show the location of the room and the place of conversation or interlocutor. Deixis time among others yindhie ‘today’, lombu ‘tomorrow’, olango ‘yesterday’, dumodupo ‘morning’, mohulonu ‘afternoon’, hui ‘night’ which have the meaning to show the time when the speech or sentence is being delivered.